1994
DOI: 10.1177/036354659402200302
|View full text |Cite
|
Sign up to set email alerts
|

The Acromion-splitting Approach for Large and Massive Rotator Cuff Tears

Abstract: A retrospective review of 42 patients in whom a rotator cuff injury was diagnosed and who subsequently underwent surgery with the superior acromion-spitting approach technique was conducted. The average size of the tear was 4.2 cm with an average tear retraction of 4.1 cm. Thirty-seven (38 shoulders) of the 42 patients underwent a physical examination, interview, and radiographs at an average followup of 33.4 months (range, 15 to 66). Using the University of California, Los Angeles Shoulder Rating Scale, 27 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…For Teflon grafts, Ozaki et al reported that 23 of 25 cases remained completely free of pain through follow-up periods that averaged 2.1 years after surgery [14]. Paulos et al studied the use of GorTex grafts, reporting one "excellent" and four "good" scores for five cases at an average of 43.2 months after the procedure [15]. In our results, pain was completely eliminated in six of nine cases with no evidence of re-tearing.…”
Section: Discussionmentioning
confidence: 99%
“…For Teflon grafts, Ozaki et al reported that 23 of 25 cases remained completely free of pain through follow-up periods that averaged 2.1 years after surgery [14]. Paulos et al studied the use of GorTex grafts, reporting one "excellent" and four "good" scores for five cases at an average of 43.2 months after the procedure [15]. In our results, pain was completely eliminated in six of nine cases with no evidence of re-tearing.…”
Section: Discussionmentioning
confidence: 99%